Enhanced mechanical strength of Cu–Sn alloy by Mg addition. (29th January 2021) - Wu, Tao; Yuan, Dawei; Huang, Hao; Wang, Wenjing; Xiao, Xiangpeng; Li, Mingmao; Yang, Bin
Abstract: In recent years, the commercially available Cu–Sn alloy has attracted great interest within the new energy vehicles and industrial robots industries because of its relatively excellent comprehensive performance as compared to those of Cu–Ag and Cu–Mg alloys. In this work, we study the possibility of improving the tensile strength of Cu–Sn alloy via Mg addition. Our results show that, the addition of Mg could significantly improve the strength of the Cu–Sn alloy, the tensile strength of the Cu–Sn alloy was increased from 399MPa to 427MPa by 0.02 wt.% Mg addition after 80% cold-rolled reduction. This can be ascribed to the combined effect of the acceleration of the grain refinement and the promotion of the sub-structures formation by Mg addition during cold rolling process. Larger number density and more uniformly distributed sub–structures with an average size of 120 nm were formed in Mg-contained alloy than that in Mg-free alloy after 80% reduction. However, the Mg addition slightly decreased the electrical conductivity (EC) of the alloy (1.5%IACS), because of the lattice distortion caused by Mg atoms.